Nanotubular Crosstalk with Distressed Cardiomyocytes Stimulates the Paracrine Repair Function of Mesenchymal Stem Cells. (3rd January 2014) - Figeac, Florence; Lesault, Pierre-François; Coz, Olivier; Damy, Thibaud; Souktani, Richard; Trébeau, Céline; Schmitt, Alain; Ribot, Jonathan; Mounier, Rémi; Guguin, Aurélie; Manier, Céline; Surenaud, Mathieu; et al.
Abstract: Mesenchymal stem cells (MSC) are known to repair broken heart tissues primarily through a paracrine fashion while emerging evidence indicate that MSC can communicate with cardiomyocytes (CM) through tunneling nanotubes (TNT). Nevertheless, no link has been so far established between these two processes. Here, we addressed whether cell-to-cell communication processes between MSC and suffering cardiomyocytes and more particularly those involving TNT control the MSC paracrine regenerative function. In the attempt to mimic in vitro an injured heart microenvironment, we developed a species mismatch coculture system consisting of terminally differentiated CM from mouse in a distressed state and human multipotent adipose derived stem cells (hMADS). In this setting, we found that crosstalk between hMADS and CM through TNT altered the secretion by hMADS of cardioprotective soluble factors such as VEGF, HGF, SDF-1α, and MCP-3 and thereby maximized the capacity of stem cells to promote angiogenesis and chemotaxis of bone marrow multipotent cells. Additionally, engraftment experiments into mouse infarcted hearts revealed that in vitro preconditioning of hMADS with cardiomyocytes increased the cell therapy efficacy of naïve stem cells. In particular, in comparison with hearts treated with stem cells alone, those treated with cocultured ones exhibited greater cardiac function recovery associated with higher angiogenesis and homing of bone marrow progenitor cells at the infarction site. In conclusion, our findings established the first relationship between the paracrine regenerative action of MSC and the nanotubular crosstalk with CM and emphasize that ex vivo manipulation of these communication processes might be of interest for optimizing current cardiac cell therapies. Stem Cells 2014;32:216–230